STATUS RESISTENSI VEKTOR FILARIASIS TERHADAP INSEKTISIDA BENDIOCARB ASAL KABUPATEN SUMBA BARAT DAYA - Julianty Almet; Diana A. Wuri; Annytha Ina Rohi Detha; Tekla D. Lanasakti (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2019)
The aim of this study is to know resistance status of filariasis vectors from Southwest Sumba to bendiocarb 0,1% insecticide. Sampling was carried out in 4 sub-districts from 11 sub-districts. The larvae were collected randomly from water containers. The collected larvae was than taken to laboratory to be maintaned until became fully grown mosquitos. As many as 25 adult mosquitos that have been took were identified to ascertain the type of mosquito suspected to be a filariasis vectors. Test of resistance to bendiocarb 0,1% was done using impregnated paper refers to the WHO method. In this test the sample was divided into two groups, namely the test group and the control group with each sample group used was 25 mosquito. The test results were obtained by counting the number of mosquitoes that knock down mosquitoes and dead mosquitoes. The test observations were recorded every 15 minutes on the first 1 hour then the observation continued for 24 post holding. The result shows that filariasis vectors from Southwest Sumba is resisten to bendiocarb 0,1% insecticide with the average percentage of deaths mosquitos of 70,27%.